STUDI PIROLISIS OFF-GRADE RUBBER DENGAN KATALIS Ni/Ga-SBA-15 MENGGUNAKAN ANALISIS TERMOGRAVIMETRI PADA LAJU PEMANASAN 10°C/MENIT - Anisa Anggraeni; R.R Dirgarini Julia Nurlianti Subagyono; Mohd. Asyraf Kassim (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
A study of off-grade rubber pyrolysis with Ni/Ga-SBA-15 catalyst using thermogravimetric analysis has been conducted. This study aims to determine the thermal decomposition process of off-grade rubber pyrolysis with Ni/Ga-SBA-15 catalyst using thermogravimetric analysis at a heating rate of 10°C/min. The pyrolysis decomposition temperature of off-grade rubber was divided into three stages, namely water evaporation at a temperature of ≤147°C, active pyrolysis at a temperature of ±147-454°C, and passive pyrolysis at a temperature of ≥454°C. Keywords: Thermogravimetric analysis, Ni/Ga-SBA-15 catalyst, Off-grade rubber